A strategy for improving the SHEPWM commutation speed of CSI through hybrid switches - Wang, Weiqi; Xia, Xiaoting; Rui, Shuling; Meng, Xiangjian; Zhang, Yumin (Frontiers in Energy Research, 2023)
High-power current source inverters (CSI) usually operate at a low switching frequency to reduce switching loss. To suppress low-order harmonics and simplify filter design, the selective harmonic elimination pulse width modulation (SHEPWM) technique is a feasible common modulation strategy in industrial applications. However, with the harmonic orders to be eliminated increase as well as the modulation index, the switching angles will become denser, and the CSIs built with low-speed switches (such as GTOs) may have difficulty for implementing the setting pulse widths of null states, so that the output current cannot reach the expected performance. This paper investigates and analyzes this phenomenon, and proposes an operational strategy that uses an H7 current source inverter (H7-CSI) with hybrid switches to perform the SHEPWM technique. On the basis of retaining the conventional H6 inverter bridge, the commutation speed of the CSI is improved by an additional shunt-connected high-performance power switch. Compared to the conventional SHEPWM-CSI solution, the proposed scheme can solve the problem of the minimum pulse width limitation, while further reducing the switching losses at an acceptable cost. In addition, mitigating the influence of overlap-time by optimizing the driving signal of the H6 converter bridge. Finally, simulation and experiments have verified the effectiveness of the proposed CSI scheme.